Sesamol: A Phenolic Compound of Health Benefits and Therapeutic Promise in Neurodegenerative Diseases - Javed, Hayate; Meeran, Mohamed Fizur N.; Jha, Niraj Kumar; Ashraf, Ghulam Md; Ojha, Shreesh (Current Topics in Medicinal Chemistry, 2024)
Sesamol, one of the key bioactive ingredients of sesame seeds (Sesamum indicum L.), is responsible for many of its possible nutritional benefits. Both the Chinese and Indian medical systems have recognized the therapeutic potential of sesame seeds. It has been shown to have significant therapeutic potential against oxidative stress, inflammatory diseases, metabolic syndrome, neurodegeneration, and mental disorders. Sesamol is a benign molecule that inhibits the expression of inflammatory indicators like numerous enzymes responsible for inducing inflammation, protein kinases, cytokines, and redox status. This review summarises the potential beneficial effects of sesamol against neurological diseases including Alzheimer's disease (AD), Parkinson's disease (PD), and Huntington's disease (HD). Recently, sesamol has been shown to reduce amyloid peptide accumulation and attenuate cognitive deficits in AD models. Sesamol has also been demonstrated to reduce the severity of PD and HD in animal models by decreasing oxidative stress and inflammatory pathways. The mechanism of sesamol's pharmacological activities against neurodegenerative diseases will also be discussed in this review.
Keywords: Alzheimer' s disease